Histamine-receptor antagonists slow 10-km cycling performance in competitive cyclists - Ely, M. R.; Sieck, D. C.; Mangum, J. E.; Larson, E. A.; Brito, L. C.; Minson, C. T.; Halliwill, J. R. (Medicine & Science in Sports & Exercise, 2019)
Histamine is released within skeletal muscle during exercise. In humans, antihistamines have no effect on speed, power output, or time-to-completion of short-duration high-intensity exercise. In mice, blocking histamine`s actions decreases speed and duration of endurance tasks. It is unknown if these opposing outcomes are the result of differences in histamine`s actions between species or are related to duration and/or intensity of exercise, as blocking histamine during endurance exercise has not been examined in humans.